2007
DOI: 10.1007/s00467-007-0456-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin retards growth and causes marked alterations in the growth plate of young rats

Abstract: Rapamycin is a potent immunosuppressant with antitumoral properties widely used in the field of renal transplantation. To test the hypothesis that the antiproliferative and antiangiogenic activity of rapamycin interferes with the normal structure and function of growth plate and impairs longitudinal growth, 4-week-old male rats (n=10/ group) receiving 2 mg/kg per day of intraperitoneal rapamycin (RAPA) or vehicle (C) for 14 days were compared. Rapamycin markedly decreased bone longitudinal growth rate (94±3 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 37 publications
2
74
1
Order By: Relevance
“…In some clinical trials in the past, similar drug concentrations were used successfully. 3 In a recently published experimental model, 22 a high intraperitoneal dosage of 2 mg/kg per d (corresponding to a weekly dosage of 14 mg/kg) was applied. We chose an intermediate dosage corresponding to 3 mg/kg per wk.…”
Section: Discussionmentioning
confidence: 99%
“…In some clinical trials in the past, similar drug concentrations were used successfully. 3 In a recently published experimental model, 22 a high intraperitoneal dosage of 2 mg/kg per d (corresponding to a weekly dosage of 14 mg/kg) was applied. We chose an intermediate dosage corresponding to 3 mg/kg per wk.…”
Section: Discussionmentioning
confidence: 99%
“…Liver samples and the proximal end of right tibias were immediately frozen in liquid nitrogen for mRNA expression studies. Left tibial proximal ends were embedded in methyl-metacrilate as previously described (2,19). Samples from one-half the animals were fixed in 40% ethanol and used for analysis of calcein and BrdU labeling.…”
Section: Methodsmentioning
confidence: 99%
“…Snout-to-tail-tip length of rats was measured at death. The longitudinal bone growth rate (m/day) during the 3 days before death was calculated by means of calcein labeling as previously described (2,19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This potent inhibition of mTOR is likely to account for the cytostatic effects of BEZ235 on MSC growth observed at higher concentrations, given the well-established role of mTOR signaling in regulating protein synthesis. (52,53) To date, the role of mTOR in osteogenesis remains controversial because conflicting studies using rapamycin have reported both negative (54)(55)(56)(57)(58)(59) and positive (24)(25)(26) effects on osteogenesis.…”
Section: Nvp-bez235 Promotes Osteogenesis In Human Mscsmentioning
confidence: 99%